Analysis of Self-Incompatibility and Genetic Diversity in Diploid and Hexaploid Plum Genotypes - Abdallah, Donia; Baraket, Ghada; Perez, Veronica; Ben Mustapha, Sana; Salhi-Hannachi, Amel; Hormaza, Jose I. (Frontiers in Plant Science, 2019)
During the last decade, S-genotyping has been extensively investigated in fruit tree crops such as those belonging to the Prunus genus, including plums. In plums, S-allele typing has been largely studied in diploid species but works are scarcer in polyploid species due to the complexity of the polyploid genome. This study was conducted in order to analyze the S-genotypes of 30 diploid P. salicina, 17 of them reported here for the first time, and 29 hexaploid plums (24 of P. domestica and 5 of P. insititia). PCR analysis allowed identifying nine S-alleles in the P. salicina samples allocating the 30 accessions in 16 incompatibility groups, two of them identified here for the first time. In addition, pollen tube growth was studied in self-pollinated flowers of 17 Tunisian P. salicina under the microscope. In 16 samples, including one carrying the Se allele, which has been correlated with self-compatibility, the pollen tubes were arrested in the style. Only in one cultivar (“Bedri”), the pollen tubes reached the base of the style. Twelve S-alleles were identified in the 24 P. domestica and 5 P. insititia accessions, assigning accessions in 16 S-genotypes. S-genotyping results were combined with nine SSR loci to analyze genetic diversity. Results showed a close genetic relationship between P. domestica and P. salicina and between P. domestica and P. insititia corroborating that S-locus genotyping is suitable for molecular fingerprinting in diploid and polyploid Prunus species.